Aristotle on the economy - Crespo, Ricardo (2010)
From seemingly outdated passages of Aristotle on oikonomikè, this paper tries to select and separate what is old-fashioned from what is valid for today. From these latter elements –which may be abridged in the intrinsic ethical and political character of economics– we can extract useful lessons. These lessons refer to the impact of Ethics and Politics on Economics. They stress the relevance of personal virtues and institutions for a suitable functioning of the economy. From an epistemological point of view, these lessons highlight the inexact character of Economics and the necessity of firm reliance on data. Current economics does not deal with ends, but only with means. The Aristotelian perspective would specially deal with ends. This concern with ends leads to prudential, not technical analysis and decisions. This calls for broadening the scope of Economics and consequently should provoke changes in its instruction. The paper concludes that a closer attention to Aristotle’s thought would have a high impact on current economy and Economics.